2023
DOI: 10.3390/jof9040492
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Morel Production upon Continuous Cropping Is Related to Changes in Soil Mycobiome

Abstract: The black morel Morchella sextelata (Morchellaceae, Pezizales) is a valuable edible mushroom that can be cultivated on a large scale, but a severe yield decline is observed during continuous cropping. The effect of long-term cropping on soil-borne diseases and the dysbiosis of the microbiome and how these biotic factors affect the morel yield are not well understood. To help fill this knowledge gap, we designed an indoor experiment to investigate the influence of black morel cropping regimes on soil physicoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Samples were collected at three stages: bare soil (BS), conidial (CD), and fruiting body primordium (PD). All soil preparation, inoculation procedures, and sample collection procedures were performed as previously described by Zhang et al (2023b) . The primordium yield was estimated by counting the number of morel primordia per 6 × 6 cm grid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples were collected at three stages: bare soil (BS), conidial (CD), and fruiting body primordium (PD). All soil preparation, inoculation procedures, and sample collection procedures were performed as previously described by Zhang et al (2023b) . The primordium yield was estimated by counting the number of morel primordia per 6 × 6 cm grid.…”
Section: Methodsmentioning
confidence: 99%
“…All soil samples were immediately frozen in liquid N and stored at −80°C until further processing. Soil physicochemical characteristics, including soil pH, organic matter content, total N, alkali-hydro N, total phosphorus, available phosphorus, and total potassium, were measured according to previously established protocols ( Zhang et al, 2023b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas species can promote mycelial growth, increase yield, and directly interact with mushrooms during the primordium stage to induce primordium formation (Cho et al, 2003 ; Kim et al, 2008 ; Zarenejad et al, 2012 ). Members of Burkholderiaceae can promote ascocarp growth during the fruiting stage (Zhang Y. et al, 2023 ). However, the soil substrate in cultivated mushrooms transmits potential pathogenic fungal taxa, including Aspergillus, Fusarium, Penicillium , and Trichoderma , leading to a decrease in yield and quality (Lo Cantore and Iacobellis, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Soil microbial biomass, diversity, and microbiota play a crucial role in continuous cropping. Changes in soil microorganisms directly affect crop growth (Zhang et al 2023). Research has shown that applying organic manure or crop residue can increase the utilization of carbon sources by soil microorganisms in paddy elds (Tang et al 2020).…”
Section: Introductionmentioning
confidence: 99%